دور الجامعات في تطوير وتنمية المجتمع - شرقي، ساجد (جامعة الكوفة - مركز دراسات الكوفة, 2011)
The issue that we are trying here addressed an important part of the structure of thought Salamis, which accounted for meta-cognitive structure, they reflect the political reality, social and economic infrastructure as are the profound reality of living in the OIC. \ The relationship between these cultural infrastructure in the area of theoretical research in the field of theology, philosophy and mysticism associated with the pattern of Islamic culture that reflects the ideological position of my faith is the absolute center comes with a dominating presence and rights conscious level II, Man is the successor to God in the management of the presence according to the letter sent by God and entrenched The instinct and reason was that the system is based on beliefs that exist She gave him a vision of faith based on the metaphysical belief in God should be absolute lesbian who is not something that came to this research in his criticism of Muslims in the citation of the absolute cross partial measure through by the absent witness with demilitarization Any perception of absolute Mahit presence. \ Research problem: a partial understanding and absolute obsession however, accompanied rights throughout history in the long struggle with the cosmic forces behind it. \ Launched be a sacred ideal, and has acquired a rise sprawl and spiritual history, and in the later stages there was a sense of a world-spiritually aware crane interfere with the daily life of man.
771612
Keywords: التدريب المهني -- الجامعات والكليات -- خدمة المجتمع -- التنمية الاجتماعية -- تنمية الموارد البشرية -- سوق العمل -- البحث العلمي